The handbook of the criminology of terrorism - LaFree, Gary; Freilich, Joshua D. (Hoboken : Wiley-Blackwell, 2016)
'The Handbook of the Criminology of Terrorism features a collection of essays that represent the most recent criminological research relating to the origins and evolution of, along with responses to, terrorism, from a criminological perspective. Offers an authoritative overview of the latest criminological research into the causes of and responses to terrorism in today$1 (Bs world Covers broad themes that include terrorism$1 (Bs origins, theories, methodologies, types, relationship to other forms of crime, terrorism and the criminal justice system, ways to counter terrorism, and more Features original contributions from a group of international experts in the field Provides unique insights into the field through an exclusive focus on criminological conceptual frameworks and empirical studies that engage terrorism and responses to it'--s
'Although there has been an explosive growth in research on terrorism across the social and behavioral sciences in the past two decades, until recently much of this work originated in political science or psychology. Some may find this surprising because terrorism clearly falls within the domain of criminology that has been defined (Sutherland and Cressey 1978:3) as encompassing research on'...the breaking of laws and reactions to the breaking of laws.' As Clarke and Newman (2006:i) succinctly put it,'Terrorism is a form of crime in all essential respects.' When we set out to compile this Handbook our main goal was to make it the source that researchers and policy experts would turn to for expert knowledge on criminological theories, methods and research on understanding the human causes and consequences of terrorism. We have aimed to make the Handbook relevant not just for scholars, but also for students, policy makers and practitioners. The Handbook should be especially useful for the growing number of classes on terrorism and homeland security that have appeared over the past 20 years. The Handbook includes six substantive sections and 36 chapters from leading researchers on the major themes and controversies in each of these sections. Individual chapters present specific topics or themes and define and describe key concepts within each section. Each chapter also outlines the current state of research by reviewing the major conceptual frameworks and empirical findings in each area. Throughout the Handbook our contributors have endeavored to highlight areas of widespread agreement within the field, as well as important debates and controversies'--
Machine generated contents note: Notes on Contributors I. INTRODUCTION Bringing Criminology into the Study of Terrorism Gary LaFree and Joshua David Freilich II. ETIOLOGY 1. The Etiology of Radicalization toward Terrorism Randy Borum 2. Psychological Factors in Radicalization: A'3N' Approach Arie W. Kruglanski and David Webber 3. What Makes Them Do It?: Individual-Level Predictors of Terrorism John P.Sawyer and Justin Hienz 4. The Terrorists' Planning Cycle: Patterns of Pre-Incident Behavior Brent Smith, Paxton Roberts and Kelly Damphousse 5. Group-Level Predictors of Political and Religiously Motivated Violence Katharine Boyd 6. Country Level Predictors of Terrorism Nancy Morris and Gary LaFree III. THEORIES 7. General Strain Theory and Terrorism Robert Agnew 8. Social Learning, Terrorism, and Terrorists: Exploring the Boundaries of a General Theory Keith Akins and L. Thomas Winfree, Jr. 9. The Situational Approach to Terrorism Henda Hsu and Graeme Newman 10. Victimization Theories and Terrorism William S. Parkin 11. Analyzing Radicalization and Terrorism: A Situational Action Theory Per-Olof H. Wikstrom and Noemie Bouhana IV. RESEARCH METHODS 12. Measuring Terrorism Laura Dugan and Michael Distler 13. Paradigmatic Case Studies and Prison Ethnography in Terrorism Research Mark S. Hamm and Ramon Spaaij 14. Social Network Analysis and Terrorism Aili Malm, Rebecca Nash and Ramin Moghadam 15. Spatial and Temporal Analysis of Terrorism and Insurgency Shane D. Johnson and Alex Braithwaite 16. The Promise of Multilevel Analysis in the Study of Terrorism Brian Johnson 17. Methodological Advancements in the Study of Terrorism: Using Latent Class Growth Analysis Nancy Morris 18. Time Series Analysis in the Study of Terrorism Henda Y. Hsu and Robert Apel V. TYPES OF TERRORISM 19. Far Right Terrorism in the United States Pete Simi and Bryan Bubolz 20. Left-Wing Terrorism: From Anarchists to the Radical Environmental Movement and Back Jennifer Varriale Carson 21. Assessing Aerial Hijacking as a Terrorist Tactic Susan Fahey 22. Evolution of Suicide Attacks Ami Pedahzur and Susanne Martin 23. Terrorist Assassinations: A Criminological Perspective Marissa Mandala VI. TERRORISM AND OTHER TYPES OF CRIME 24. Organized Crime and Terrorism Enrique Desmond Arias and Nazia Hussain 25. Similar from a Distance: A Comparison of Terrorism and Hate Crime Ryan D. King, Laura M. DeMarco and Robert J. Vanden Berg 26. Studying Extremist Homicide in the United States Jeff Gruenewald and Brent Klein 27. Financing Terror: Financial Schemes Involving Far-Right and Jihadi Extremists Brandon A. Sullivan, Joshua David Freilich and Steven Chermak 28. An Empirical Analysis of Maritme Piracy using the Global Terrorism Database Bo Jiang VII. COUNTERING TERRORISM 29. Empowering Communities to Prevent Violent Extremism: A Report on the Ape August 2014 National Summit William Braniff and Steven Weine 30. Terrorist Plots Against the US: What We Have Really Faced, and How We Might Best Defend Against It Kevin Strom, Mark Pope and John S. Hollywood 31. The Ten Commandments for Effective Counterterrorism Simon Perry, David Weisburd and Badi Hasisi 32. Prosecuting Terrorism Post-9/11: Impact of Policy Changes on Case Outcomes Christopher Shields, Brent Smith and Kelly Damphousse 33. Prisons: Their Role in Creating and Containing Terrorists Margaret A. Zahn 34. The Individual Risk Assessment of Terrorism: Recent Developments John Monahan 35. Legislative Efforts to Intervene and Prevent Eco-Terrorist Attacks Sue-Ming Yang and Yi-Yuan Su 36. On the Relevance of Cyber Criminological Research in the Design of Policies and Sophisticated Security Solutions against Cyber-Terrorism Events David Maimon and Alexander Testa Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Criminology; Terrorism -- Research; Terrorism -- Prevention; SOCIAL SCIENCE / Criminology; Criminology; Terrorism -- Prevention; Terrorism -- Research; Electronic books